Low-dose AtropIne for Myopia Control in Children (AIM): protocol for a randomised, controlled, double-blind, multicentre, clinical trial with two parallel arms - Farassat, Navid; Böhringer, Daniel; Küchlin, Sebastian; Molnár, Fanni E.; Schwietering, Anne; Seger, Dorina; Hug, Martin J.; Knöbel, Anja-Birte; Schneider-Fuchs, Sabine; Ihorst, Gabriele; Wabbels, Bettina Kathrin; Beisse, Christina; et al. (BMJ open, 2023)
Introduction Myopia is a major cause of degenerative eye disease and increases the risk of secondary visual impairment. Mitigating its progression therefore has great potential of clinically relevant benefit as shown by using highly diluted atropine eye drops in children of Asian origin. However, limited evidence is available regarding the efficacy and safety of low-dose atropine therapy in non-Asian populations. Hence, the Low-dose AtropIne for Myopia Control in Children (AIM) study will test the efficacy and safety of 0.02% atropine vs placebo in a German population. - Methods and analysis AIM is a national, multicentre, prospective, randomised, placebo-controlled, double-blind trial with two parallel arms. The primary objective is to assess the efficacy of atropine 0.02% eyedrops for myopia control in children of Caucasian origin. The primary outcome is the change in cycloplegic refraction after 1 year of treatment (D/year). Secondary and tertiary outcome measures comprise the change in axial length (mm/year) in children treated with 0.02% atropine compared with placebo, the myopic progression of participants treated with 0.01% compared with 0.02% atropine (D/year and mm/year), and the safety profile of both 0.02% and 0.01% atropine. Furthermore, the myopic progression 1 year after cessation of therapy with 0.02% atropine will be evaluated. Inclusion criteria are an age of 8-12 years and myopia of −1 D to −6 D with an estimated annual myopia progression of ≥0.5 D. After randomisation, patients will receive either atropine 0.02% (arm A) or placebo eye drops (arm B) in the first year of treatment. In the second year, they will continue to receive atropine 0.02% (arm A) or switch to atropine 0.01% (arm B). In the third year, they will switch to placebo (arm A) or continue with atropine 0.01% (arm B). To achieve a statistical power of 80%, the calculated sample size is 300. The trial has started in October 2021 with a planned recruitment period of 18 months. - Ethics and dissemination AIM has been approved by the Central Ethics Committee of the University Medical Center Freiburg (21-1106), local ethics committees of each participating centre and the German Federal Institute for Drugs and Medical Devices (61-3910-4044659). It complies with the Declaration of Helsinki, local laws and ICH-GCP. Results and underlying data from this trial will be disseminated through peer-reviewed publications and conference presentations. - Trial registration number NCT03865160.